Determining the coordinates of a mobile robot in an industrial space using BLE technology based on RSSI data received from base stations - Nevliudov, I.Sh.; Novoselov, S.P.; Sychova, O.V.; Tesliuk, S.I. (Radiotekhnika, 2022)
Existing global positioning technologies cannot be applied indoors, where the signal from satellites or communication towers is significantly reduced or completely absent due to signal weakening in the walls of the building. Wireless network technologies such as Bluetooth or Wi-Fi can also be used in the process of local determining the mobile platforms position in industrial premises. But such methods have a problem with providing the required accuracy. The relevance of these studies is associated with solving the problem of local positioning of mobile robots in a room with an accuracy of ten centimeters. The article presents a comparative analysis of determining coordinates’ principles by the AOA, TOA, TDOA and RSSI methods. It is proposed to use BLE technologies based on the RSSI data received from base stations. Using the triangulation method, formulas are obtained for solving the problem of determining the coordinates of an object moving in space. The software and hardware complex architecture has been developed. It is proposed to use ESP32 modules as base radio stations. The RSSI value is very unstable, so the positioning accuracy will depend on the number of base stations and the additional software tools used.